2017
DOI: 10.1136/heartjnl-2016-310699
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and warfarin therapy at two anticoagulation clinics in Brazil

Abstract: Objective Health literacy has been related to health-related conditions and health outcomes. Studies examining the association of health literacy and anticoagulation have had variable results. We sought to investigate the relations of health literacy and percentage of time in therapeutic range (TTR) in a vulnerable Brazilian cohort at two hospital-based anticoagulation clinics. Methods We measured health literacy with the Short Assessment of Health Literacy for Portuguese-speaking Adults (SAHLPA-18) in 2015–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 24 publications
0
29
0
15
Order By: Relevance
“…In this study, the Flesch Index revealed that the texts were suitable for users who have a high level of reading to understand the published information. In Brazil, approximately 50% of the population has completed elementary education and one third presents low functional literacy (20). Information is more easily understood when there is a predominance of short sentences and a substitution of technical words by simpler ones.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the Flesch Index revealed that the texts were suitable for users who have a high level of reading to understand the published information. In Brazil, approximately 50% of the population has completed elementary education and one third presents low functional literacy (20). Information is more easily understood when there is a predominance of short sentences and a substitution of technical words by simpler ones.…”
Section: Discussionmentioning
confidence: 99%
“…PHC is the first contact between population and health service and, in Brazil, the prevention, diagnosis, monitoring and control of the blood pressure pose challenges to the teams of Basic Attention (BA). The professionals of BA shall focus on the user's participation in the treatment, involving him/her in the definition and implementation of strategies to control high blood pressure (17) . Given this context, the HL of users contributes greatly to text reading and comprehension of the written and oral information provided by doctors, nurses and other health professionals to make decisions, use medicines properly and/or perform self-care (14) .…”
Section: Introductionmentioning
confidence: 99%
“…We chose the SAHLPA instrument because it is shorter (18 items) and more practical to apply than the others, and it has satisfactory psychometric properties. [20][21][22] All two tools have limitations, as they are restricted to medical terms and do not evaluate other HL skills, such as conceptual knowledge, and critical, interactive and mathematical skills. 22,28 There is also no standard instrument for the assessment of HL in the context of hypertension, but previous studies have used S-TOFHLA, 15,17 the Rapid Estimate of Adult Literacy in Medicine (REALM), 1,14,18 and the Brief Health Literacy Screen (BHLS).…”
Section: Discussionmentioning
confidence: 99%
“…16 The SAHLPA instrument was used in cross-sectional studies with diabetic patients at primary healthcare level 22 and patients undergoing anticoagulant therapy at tertiary healthcare level. 21 HL is a new research field. LHL is directly associated to worse health outcomes and greater use of health services.…”
Section: Discussionmentioning
confidence: 99%